EMPIRICAL EQUATION FOR PREDICTING FRACTURE FREQUENCY OF CARBONATE AND SILICATE ROCKS USING P-WAVE VELOCITY - Sari Melati; Ridho K. Wattimena; David P. Sahara; Ganda M. Simangunsong; Wahyu Hidayat (Rudarsko-geološko-naftni Zbornik, 2025)
Fracture frequency (FF) is necessary for fracture quantification in rock mass classification systems and plays an important role in the mechanical properties of rock mass. To date, laboratory studies on the effects of jointed rock on rock velocity have been limited to high FF conditions and have not incorporated lithological variations. This study aimed to estimate the FF indirectly by determining its relationship with wave velocity in carbonate and silicate rocks. Two carbonate (CA1 and CA2) and two silicate (CR1 and CR2) rocks were drilled from four sites on the Java Island in Indonesia, and their characteristics were identified through petrographic tests, physical property measurements, and ultrasonic velocity tests. Artificial joints were made in the core samples of these rocks to create varying joint spacing, especially at low frequencies between 0 and 24 joints per metre. We successfully obtained new empirical equations expressing the relationship among the FF, intact rock P-wave velocity (Vp0), and jointed rock P-wave velocity (Vpj). For CA1, CA2, CR1, and CR2, the Vpj/Vp0 ratios were 1–0.0172FF, 1–0.0301FF, 1–0.0371FF, and 1–0.0349FF, respectively. The coefficient of determination of the equation for each lithology showed that the porosity, velocity, and density affected the fitting of the data to the equation. Overall, the findings of this study can be used to optimise the utilisation of geophysical methods for geotechnical monitoring, especially the identification of FF in lithology contrast between carbonate and silicate rocks or rocks with different compaction levels.